ANALISIS KUALITAS LAYANAN DAN KEPUASAN ORANG TUA TERHADAP PROGRAM TERAPI WICARA DI KLINIK TUMBUH KEMBANG ANAK - Utamie, Anggriyani; Zakky Zamrudi; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
Speech impairments in Children with Special Needs (CSN) necessitate professional, high-quality intervention. This study aims to analyze the service quality gap (SERVQUAL), identify the dominant factors determining parental satisfaction, and measure the overall satisfaction level with the speech therapy program.Method: This research employed a quantitative descriptive approach using a cross-sectional survey design. The population consisted of parents with children actively undergoing speech therapy at Clinic X, selected through purposive sampling. Data were collected using structured questionnaires measuring five service quality dimensions. Data analysis included gap analysis, descriptive statistics, and multiple regression analysis.Results: Gap analysis revealed that perceived service quality did not fully meet parental expectations, evidenced by a negative gap in almost all dimensions. The most severe gaps were found in the Empathy and Reliability dimensions. Multiple regression analysis confirmed that Reliability (administrative consistency) and Empathy (emotional support) were the two most dominant and significant factors influencing overall parental satisfaction (p < 0.05). However, the overall parental satisfaction level (aggregate) was categorized as High (90% Satisfied/Very Satisfied).Conclusion: The high overall satisfaction, despite process shortcomings, is explained by the Expectation Disconfirmation Theory, where the positive clinical outcomes observed in the child's development outweigh the deficiencies perceived in the service process. The main recommendation for the clinic is to prioritize improving Reliability through procedural standardization and strengthening Empathy via supportive communication training to achieve Service Quality Excellence.